2008
DOI: 10.1200/jco.2006.08.8799
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Childhood Ganglioneuroma

Abstract: Diagnosis was changed to GNBI for approximately one third of 76 reviewed tumors. Patients with confirmed GN, reclassified as GNBI, and nonreviewed histology presented with comparable clinical, biochemical, and biologic features. Surgical results, complication rate, number of progressions, and outcome were similar for the three groups. Surgery was associated with significant risk of complications. Survival was not influenced by extent of tumor resection. Aggressive surgical approach should not be recommended fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
135
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 19 publications
(19 reference statements)
12
135
4
4
Order By: Relevance
“…Five patients showed MIBG uptake at the end of treatment, but became negative during the follow-up course. De Bernardi et al (25) have reported in a retrospective study that the uptake of MIBG was recognized in 36.4% of ganglioneuromas. This is consistent with our results.…”
Section: A At Diagnosismentioning
confidence: 99%
“…Five patients showed MIBG uptake at the end of treatment, but became negative during the follow-up course. De Bernardi et al (25) have reported in a retrospective study that the uptake of MIBG was recognized in 36.4% of ganglioneuromas. This is consistent with our results.…”
Section: A At Diagnosismentioning
confidence: 99%
“…While early-stage tumors are treated effectively and may regress spontaneously, survival in patients with advanced-stage tumors is below 40% (2,3). Clinical heterogeneity and treatment morbidity (4,5) have driven the development of genetic and molecular screening approaches to identify children who may be spared intensive therapy (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In human, ganglioneuromas tend to occur in children and adolescents and are commonly located in the thorax or abdomen [3,11]. In dogs, ganglioneuromas most commonly tend to occur in the central nervous system, followed by the alimentary tract, and the peripheral nervous system; in other animals such as cats, horses, and pigs, the alimentary tract is the most common site [1,5,6,12,15].…”
mentioning
confidence: 99%